Influence of calcination temperature on the physicochemical properties of synthesized hydroxyapatite from cow bone waste - Mohamad Dom, Adibah Haneem; Rezadin, Salman; Abd Rahim, Toibah; Shamsudin, Zurina; Shamsuri, Siti Rahmah; Alhamoudi, Fahad Hussain (Penerbit Akademia Baru, 2024)
The chemical similarity found in hydroxyapatite (HA) with natural bone makes it a popular choice for bone replacement. Therefore, in recent years, there has been an increasing tendency towards manufacturing HA from biological sources or waste, such as animal bone waste. Using naturally derived HA can benefit the economy, the environment, and human health. Therefore, this paper reports on the extraction of HA from cow bone waste using a simple and cost-effective technique. The bone powder was calcined in a furnace at temperatures ranging from 700°C to 1000°C for two hours. Then, the synthesized HA was characterized using a Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-ray Spectroscopy (EDX), Fourier Transform Infrared Spectroscopy (FTIR), and X-ray diffraction (XRD). FESEM images revealed that HA particles with non-uniform spherical morphology were produced where the size increases with the calcination temperature. This finding is consistent with the average value of particle diameter measured at a temperature of 1000°C (0.783±0.268 µm) which is much greater than at a temperature of 700°C (0.272±0.128 µm). EDX analysis revealed that the Ca/P ratio value obtained in this study indicates non-stoichiometric HA production. XRD analysis shows that only the HA phase is present and there is no secondary phase generated from the calcination process. Meanwhile, FTIR analysis can detect the main group elements of the HA which were OH- and PO4 3-. The findings obtained in this study prove the effectiveness of this method in producing highly crystalline HA powder from cow bone waste using the thermal treatment method.